Porous Perovskite Fibers – Preparation by Wet Phase Inversion Spinning and Catalytic Activity. Issue 7 (6th June 2014) - Kaiser, Sandy; Reichelt, Erik; Gebhardt, Sylvia E.; Jahn, Matthias; Michaelis, Alexander
Abstract Porous perovskite (LaMnO3) fibers were prepared by means of wet phase inversion spinning. The influence of different spinning procedures, slurry and coagulation bath composition on fiber shape and pore morphology was studied. The catalytic activity of the prepared fibers was tested for carbon monoxide oxidation as a model reaction in a differential recycle reactor. The results revealed that by suitable choice of process conditions porous catalytically active fibers can be prepared. Catalytic measurements confirmed that the catalytic fibers exhibit an open structure that allows full utilization of the catalytically active surface without intraparticle diffusional limitations.